Sensitivity and Specificity of Auramin-Rhodamin Stain for Diagnosis of Pleural Tuberculosis - Sultana, Mst Mahfuza; Naher, Akhtarun; Paul, Shikha; Tangim, Shaharat Farha; Hossain, Md Enamul; Khan, Tarina; Sultana, Sharmin (Journal of Enam Medical College, 2024)
Background: Tuberculosis remains a major public health problem in Bangladesh. Among the extra-pulmonary tuberculosis (EPTB), pleural is the second most common site. Tubercular pleural effusion may cause a diagnostic dilemma as mycobacterium could not be detected in most cases due to paucibacillary nature of effusion. Sensitivity of detection of AFB in pleural fluid by microscopy is very low. Objective: To evaluate the sensitivity and specificity of Auramine-Rhodamine staining. Materials and Methods: This cross-sectional analytical study was based on 183 specimens of pleural fluid which was collected from the patient of suspected pleural tuberculosis at Institute of Disease of the Chest and Hospital (NIDCH). After collection, the specimens were processed and stained with Auramine-Rhodamine staining method and cultured on MGIT960 medium. Results: Among 183 specimens, 09 (4.9%) were found positive by Auramine-Rhodamine stain and 16 (8.7%) samples were positive for growth on MGIT960 medium. Sensitivity and specificity of Auramine-Rhodamine staining was 56.3% and 100% respectively. Conclusion: This study demonstrates that Auramine-Rhodamine staining method may be a useful method where culture facilities are not available. J Enam Med Col 2022; 12(1): 24−28